Clinical outcomes of endoscopic ultrasound-guided ethanol ablation for pancreatic cystic lesions compared with the natural course: a propensity score matching analysis - Jin Ho Choi; Sang Hyub Lee; Young Hoon Choi; Jinwoo Kang; Woo Hyun Paik; Dong-Won Ahn; Ji Kon Ryu; Yong-Tae Kim (Therapeutic Advances in Gastroenterology, 2018)
Background Endoscopic ultrasound-guided ethanol ablation (EUS-EA) is a recently introduced treatment for pancreatic cystic lesions (PCLs). However, clinical benefits such as survival gain and maintenance of quality of life (QOL) have not been fully established. The aim of this study was to evaluate the clinical benefits of EUS-EA compared with the natural course (NC) of PCLs. Methods This retrospective comparative study of patients with PCLs investigated an EUS-EA group ( n = 118) and an NC group ( n = 428). Propensity score matching (PSM) analysis was applied to minimize the effects of selection bias. The overall survival as the primary outcome and the surgical resection rate and complete remission (CR) rate as the secondary outcomes were evaluated. Results Between 84 matched pairs of both groups, there were no significant differences in the baseline clinical characteristics and the mean follow-up duration (78.88 ± 38.86, 75.90 ± 57.46 months, p = 0.694). Overall survival did not differ significantly (194.12 ± 5.60, 247.54 ± 12.70 months, p = 0.235). The surgical resection rate (4.8% versus 26.2%, p < 0.001) was significantly lower in the EUS-EA group. CR was observed only in the EUS-EA group and the CR rate was 32.1%. Conclusions EUS-EA for PCLs with low risk of malignancy might not be able to obtain a survival benefit, but showed maintenance of QOL by avoidance of unnecessary surgery, and a certain level of CR when compared to the NC. EUS-EA could be considered a useful treatment option for these, but careful application is needed because of the limited effects in some types of PCLs.